DESIGN OF AN HTS SUPERCONDUCTING ELECTROMAGNET INTENSE AND UNIFORM MAGNETIC FIELD GENERATOR (ELECTRICAL MACHINES, MATERIALS AND DRIVES — PRESENT AND TRENDS, 2023)
The paper presents the important elements for the design of an HTS superconducting electromagnet, generator of an intense magnetic field (5T) and of high uniformity (
Keywords: Superconductive; intense magnetic field; Cryogenics